Effectiveness of various irrigant activation techniques on the penetration of sodium hypochlorite into lateral canals of mature permanent teeth: A systematic review and meta-analysis - Ram Surath Kumar; Anil V. Ankola; Roopali M. Sankeshwari; Mamata Hebbal; Vinuta Hampiholi; Lokesh Kumar S; Apurva Prashant Deshpande; Abhra Roy Choudhury; Atrey J. Pai Khot (Elsevier, 2023)
Objective: This review aimed to systematically review the effectiveness of various irrigant activation techniques (IATs) on the penetration of sodium hypochlorite (NaOCl) into the lateral canals of mature permanent teeth. Methods: Electronic databases including MEDLINE (via PubMed), Scopus, ProQuest, and Cochrane Library were searched to identify laboratory studies evaluating the penetration of NaOCl into lateral canals following the use of apical negative pressure irrigation (ANP), passive ultrasonic irrigation (PUI), sonic irrigation (SI), and/or manual dynamic activation (MDA) techniques. Meta-analysis was performed for individual IATs in comparison with CNI into the lateral canals of both straight and curved root canals. On the basis of the previous literature and parameters, the risk of bias of the selected studies was evaluated with the help of a customized tool. Results: Of the 983 records screened, 12 studies were selected to include in the systematic review, and 10 studies were selected for the meta-analysis. The total quality assessment across the included studies indicated a high quality (83.3%). Overall, the meta-analysis demonstrated IATs had significant improvement in the penetration of NaOCl into the lateral canals of straight canals (34.3%) over CNI. The subgroup analysis of individual IATs demonstrated PUI (60.9%) to be superior in the penetration into lateral canals of straight canals. Conclusions: IATs improved the irrigant penetration into lateral canals and therefore their use during routine endodontic practice is recommended. In straight canals, PUI is the most effective IAT followed by ANP, SI, and MDA techniques.